Spectral modeling of rotating turbulent flows - Baerenzung, J. (2010)
A subgrid-scale spectral model of rotating turbulent flows is tested against direct numerical simulations (DNSs). The case of Taylor-Green forcing is considered, a configuration that mimics the flow between two counter-rotating disks as often used in the laboratory. Computations are performed for moderate rotation down to Rossby numbers of 0.03, as can be encountered in the Earth's atmosphere. We provide several measures of the degree of anisotropy of the small scales and conclude that an isotropic model may suffice at moderate Rossby number. The model, developed previously [J. Baerenzung, H. Politano, Y. Ponty, and A. Pouquet, "Spectral modeling of turbulent flows and the role of helicity," Phys. Rev. E77, 046303 (2008)], incorporates eddy viscosity and eddy noise that depend dynamically on the index of the energy spectrum. We show that the model reproduces satisfactorily all large-scale properties of the DNS up to Reynolds numbers of ~104 and for long times after the onset of the inverse cascade of energy; it is also shown to behave better than either the Chollet-Lesieur eddy viscosity model [J. P. Chollet and M. Lesieur, "Parametrization of small scales of three-dimensional isotropic turbulence utilizing spectral closures," J. Atmos. Sci.38, 2747 (1981)] or an under-resolved DNS. © 2010 American Institute of Physics.